Endoplasmic Reticulum Stress Is Involved in Baicalin Protection on Chondrocytes From Patients With Osteoarthritis - Jiangang Cao; Yu Zhang; Tianyi Wang; Bo Li (Dose-Response, 2018)
Osteoarthritis (OA) affects elderly population worldwide and endoplasmic reticulum (ER) stress is known to be positively correlated with OA development. Previous reports prove the cytoprotective effects of baicalin on chondrocytes, whereas the mechanisms are hardly reported. Hence, we aimed to investigate the links between OA, ER stress, and baicalin. Chondrocytes from patients with OA were subjected to H 2 O 2 treatment with or without baicalin pretreatment, and cell viability was assessed via Cell Counting Kit-8. Messenger RNA (mRNA) amounts of apoptosis-related genes (Bax, Bcl-2, and Caspase-3), extracellular matrix (ECM)-related genes (Collange I, Collange II, Aggrecan, and Sox9) and ER stress hallmarks (binding immunoglobulin protein [BiP] C/EBP homologous protein [CHOP]) were evaluated via quantitative real-time PCR. Bax, Bcl-2, BiP, and CHOP protein levels were analyzed via Western blot. Baicalin suppressed the changes in cell viability and apoptosis-related gene expressions caused by H 2 O 2 . Reactive oxygen species and glutathione/oxidized glutathione assay showed that H 2 O 2 enhanced oxidative stress. Baicalin suppressed H 2 O 2 -induced downregulation of mRNA expression of ECM-related genes. Moreover, baicalin reduced H 2 O 2 -stimulated increase in oxidative stress and the expression of ER stress hallmarks. Endoplasmic reticulum stress inducer abolished the protective activities, whereas ER stress inhibitor did not exhibit extra protective effects. Baicalin pretreatment protected patient-derived chondrocytes from H 2 O 2 through ER stress inhibition.